Member - Chrysostomou, Christis (My University, 2026)
The committee prepared a document in which the earthquake safety standards were established and which was used to screen schools. This document defined among other things the minimum acceptable strengths of the materials, the required earthquake loading, the methodology for taking the decision for keeping / demolishing buildings and methods for their retrofitting / strengthening